"It's Not All About My Baby's Sleep": A Qualitative Study of Factors Influencing Low-Income African American Mothers' Sleep Quality. Issue 5 (2nd September 2016) - Zambrano, Danielle N.; Mindell, Jodi A.; Reyes, Naomi R.; Hart, Chantelle N.; Herring, Sharon J.
Abstract : Low-income African American mothers are at particular risk for poor postpartum sleep. This study sought to understand facilitators and barriers that exist to getting a good night's sleep among these high-risk mothers. Semistructured interviews with 18 low-income African Americans (3–6 months postpartum) were conducted. Most mothers described their own sleep quality to be poor, despite the fact that their babies' sleep improved substantially from the newborn period. Mothers kept themselves awake due to their own internal worry and anxiety, along with external factors that were largely independent of babies' sleep, including work and school commitments and the home environment. For the few mothers with good sleep quality, time management and family support were strong facilitators. Findings lay the groundwork for sleep improvement interventions.